Translation and society: an introduction - Sergey Tyulenev (London: Routledge, 2014)
"This essential new textbook guides readers through the social aspects and sociologically informed approaches to the study of translation.Sergey Tyulenev surveys implicitly and explicitly sociological approaches to the study of translation, drawing on the most important and influential works both within translation studies and in sociology, as well as recent developments in the field. In addition to the theoretical grounding provided, the book explains in detail the methodology of studying translation from a sociological point of view.Translation and Society discusses why translation should be studied sociologically, reinforces the foundation of the sociologically informed translation research already in existence in the field and outlines possible new directions for the future. Throughout the book there are many examples and case studies and each chapter includes thought-provoking discussion points, possible assignments, and suggestions for further reading. This is an invaluable textbook for undergraduate and postgraduate students of Translation Studies. "--
Keywords: Translating and Interpreting; Translation; Sociolinguistics; Languages